QUANTIFYING THE DIFFUSION KINETICS AND SPATIAL DISTRIBUTIONS OF RADIOGENIC 4HE IN MINERALS CONTAINING PROTON-INDUCED 3HE - Shuster D.L.; Farley K.A.; Sisterson J.M.; Burnett D.S. (My University, 2004)
Apatite, titanite and olivine samples were bombarded with a ~150 MeV proton beam to produce ~108 atoms/mg of spallation 3He. High-precision stepped-heating experiments were then performed in which the artificial 3He and, for apatite and titanite, the natural radiogenic 4He were measured to characterize the diffusive behavior of each isotope. Helium-3 diffusion coefficients are in excellent agreement with concurrently and/or previously determined He diffusion coefficients for each mineral. Our results indicate that proton-induced 3He is uniformly distributed and that radiation damage associated with a proton fluence of ~5x1014 protons/cm2 does not cause noticeable changes in 4He diffusion behavior in at least apatite and titanite. Proton-induced 3He can therefore be used to establish He diffusion coefficients in minerals with insufficient natural helium for analysis or those in which the natural 4He distribution is inhomogeneous. In addition, step-heating 4He/3He analysis of a mineral with a uniform synthetic 3He concentration provides a means by which a natural 4He distribution can be determined.
Keywords: HELIUM; DIFFUSION; THERMOCHRONOMETRY; ISOTOPE; PROTON BEAM; (U-TH)/HE